Application of Multi-Objective Method in E-Sports Tourism Industry - Xianglan Hu, Yunbao Xu, Qiuzhen Wang (Forest Chemicals Review)
In the development of e-sports tourism, one of the problems to be solved is the scheduling of e-sports competitions. Global e-sports has attracted the attention of game fans all over the world. Due to the existence of time difference, how to achieve the ideal order of the competition scheduling is particularly important. On account of the time zone difference of fans, arranging the championship optimally is of vital importance. E-sports championship timetabling problem (ECTP) is a kind of timetabling problem. Usually, championships are arranged by experienced competition managers, which is not optimal. Intelligent algorithms are advanced heuristic methods that are very effective in many fields. But up till now, there hasn’t someone who researches its application in this area. So in this paper, we first need to put forward a new mathematical model to this problem, and then we propose two evaluation function in this model. After taking the characteristic of this problem into account, we consider Multi-objective evolutionary Algorithm Based on Decomposition a great algorithm to solve this problem. But it is not suitable at first, so we made plenty of improvements, such as changing the coding method, population initialization, and genetic operation. The comparison with other algorithms shows that it has better performance in nearly all cases.